2017
DOI: 10.1111/bcpt.12749
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol Attenuates Concanavalin A‐induced Hepatic Fibrosis, Inhibits CD4+ T Helper 17 (Th17) Cell Differentiation and Suppresses Hepatic Stellate Cell Activation: Blockade of Smad3/Smad4 Signalling

Abstract: Magnolol is a pharmacological biphenolic compound extracted from Chinese herb Magnolia officinalis, which displays anti-inflammatory and antioxidant effects. This study was aimed at exploring the potential effect of magnolol on immune-related liver fibrosis. Herein, BALB/c mice were injected with concanavalin A (ConA, 8 mg/kg/week) up to 6 weeks to establish hepatic fibrosis, and magnolol (10, 20, 30 mg/kg/day) was given to these mice orally throughout the whole experiment. We found that magnolol preserved liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Of note, the AIMP1 peptide did not influence TGF-β-induced phosphorylation of SMAD2 and SMAD3 but inhibited the nuclear translocation of SMAD3 by a still not identified mechanism [264]. Moreover, Zhang and his colleagues used magnolol to prevent the interaction between SMAD3 and SMAD4 and, thus, could attenuate TGF-β signaling and concanavalin A induced hepatic fibrosis [265]. In line with the above description on the distinct roles of SMAD3 and SMAD2 in organ fibrosis, a recent study reported the efficacy of a specific SMAD3 inhibitor (SIS3) in reducing fibrosis, apoptosis, and inflammation in a mouse model of kidney fibrosis [266], however, a therapeutic effect of SIS3 on liver fibrosis still remains poorly defined.…”
Section: Targeting Tgf-β In Liver Fibrosismentioning
confidence: 99%
“…Of note, the AIMP1 peptide did not influence TGF-β-induced phosphorylation of SMAD2 and SMAD3 but inhibited the nuclear translocation of SMAD3 by a still not identified mechanism [264]. Moreover, Zhang and his colleagues used magnolol to prevent the interaction between SMAD3 and SMAD4 and, thus, could attenuate TGF-β signaling and concanavalin A induced hepatic fibrosis [265]. In line with the above description on the distinct roles of SMAD3 and SMAD2 in organ fibrosis, a recent study reported the efficacy of a specific SMAD3 inhibitor (SIS3) in reducing fibrosis, apoptosis, and inflammation in a mouse model of kidney fibrosis [266], however, a therapeutic effect of SIS3 on liver fibrosis still remains poorly defined.…”
Section: Targeting Tgf-β In Liver Fibrosismentioning
confidence: 99%
“…IL-17 signaling facilitated the production of multiple cytokines including TGF-β, and directly induced production of collagen in HSCs through activation of signal transducers and activators of transcription (STAT) 3 signaling pathway [ 91 ]. Inhibition of Th17 cells by small molecules Halofugine and Magnolol significantly reduced the severity of Concanavalin A-induced liver fibrosis, suggesting that Th17 cells may represent novel therapeutic targets for treating liver fibrosis [ 92 , 93 ].…”
Section: Adaptive Immune Cells In the Pathogenesis Of Fibrosismentioning
confidence: 99%
“…In vitro research showed that 12.5–50 μ mol/L honokiol induced apoptotic death in activated rat HSCs through the release of mitochondrial cytochrome C [ 140 ]. Magnolol also attenuated ConA-induced liver fibrosis and suppressed human LX2 HSC activation, which was closely related to inhibiting Th17 cell differentiation by suppressing IL-17A generation [ 141 ]. In addition, other honokiol derivatives, such as 4′-O-methylhonokiol, also prevented from HSC activation and induced apoptosis via regulation of Bak1 and Bcl-2 expression [ 142 ].…”
Section: Lignansmentioning
confidence: 99%